Intercultural Communication, Variation in Translation and its Linguocultural Adaptation - Tomash Vrabel; Vrábely Tamás; Врабель Томаш (CPN Publishing Group, 2020)
Abstract. The article introduces the analysis of intercultural communication, variation in translation and its linguocultural adaptation. The author focuses on the causes of misunderstanding in the course of intercultural communication and ways to avoid it. The process of linguocultural adaptation of translation is analysed to give a clear view of the difficulties translators face in literary translation. Furthermore, variations in translation are discussed in connection with the communicative paradigm of translation. We have come to the conclusion that differences in understanding the translated text by different addressees can be related to the original pragmatic settings of the translator who may reproduce just the surface sense of the original or the implications as well.
Keywords: intercultural communication; translation; communicants; cultural conventions; linguocultural adaptation; pragmatic adaptation; variation in translation